Electrical properties of digital-alloy (AlxGa1-x)As/GaAs during molecular beam epitaxy growth - Kim, Jin Soak; Kim, Eun Kyu; Song, Jin Dong; Lee, Jung Il (KOREAN PHYSICAL SOC, 2007)
We have investigated the electrical properties of digital-alloy AlGaAs on GaAs by using capacitance-voltage (C-V) and deep-level transient spectroscopy (DLTS) methods. During molecular beam epitaxy growth, digital-alloy and analogue-alloy samples were prepared. The digital-alloy layer consists of hundreds of AlAs and GaAs layers each thickness of 2 monolayers. Most properties of the digital alloy were similar to the analogue alloy, but some electrical properties from these of digital-alloy were quite different to the analogue-alloy from the C-V and low-temperature DLTS measurements. Especially, the superlattice structures slightly interrupt carrier motion at low temperatures (< 80 K); then, a signal whose origin seems to be a hetero barrier of the GaAs/AlGaAs quantum well is found, and its average activation energy is estimated to be about 45 meV.
Keywords: OPTICAL-PROPERTIES; ROOM-TEMPERATURE; LASERS